PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN BISKUIT OREO DI CARREFOUR SURABAYA) - VIDYA PURNAMA SARI, HERVIANA (Jurnal Ilmu Manajemen (JIM), 2018)
Biscuits is the company in the industrial sector food products that are now often popular by the consumers that can be consumed by when leisure time or the to hold hungry and for all the age of a boy , up to the elderly .This study attempts to analyze and discuss the influence of product quality and price of loyalty with satisfaction as variable intervening.The applied sampling technique was non-probability sampling and judgmental sampling on samples as many as 220 individuals. Population is now consumers who aged 17 years and above ever buy and consume biscuit oreo.The result showed that the product quality and price oreo biscuit having influence that give a positive response to loyalty.The quality and price of the product have influence that give a positive response to satisfaction.The satisfaction of having an influence that give a positive response to loyalty . In this study, the relationship of each variable is positive that mediation proved partially. Keywords: quality products, price, satisfaction, loyalty